2020
DOI: 10.3390/ijms21165912
|View full text |Cite
|
Sign up to set email alerts
|

Na+, K+-ATPase α Isoforms and Endogenous Cardiac Steroids in Prefrontal Cortex of Bipolar Patients and Controls

Abstract: Bipolar disorder is a chronic multifactorial psychiatric illness that affects the mood, cognition, and functioning of about 1–2% of the world’s population. Its biological basis is unknown, and its treatment is unsatisfactory. The α1, α2, and α3 isoforms of the Na+, K+-ATPase, an essential membrane transporter, are vital for neuronal and glial function. The enzyme and its regulators, endogenous cardiac steroids like ouabain and marinobufagenin, are implicated in neuropsychiatric disorders, bipolar disorder in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Subsequently, we have demonstrated a significant association with BD of six single SNPs in the three genes of the Na + , K + -ATPase α isoforms. Haplotype analysis of the α2 isoform showed a significant association with two loci haplotypes pertaining to BD, suggesting that this enzyme plays a role in the etiology of the disease [91], and, indeed, this isoform appears to be reduced in the temporal cortex of individuals with bipolar disorder [92], but α2 and α3 may be increased in the prefrontal cortex [20].…”
Section: Role Of Ecs In Humans Mood Disordersmentioning
confidence: 97%
See 2 more Smart Citations
“…Subsequently, we have demonstrated a significant association with BD of six single SNPs in the three genes of the Na + , K + -ATPase α isoforms. Haplotype analysis of the α2 isoform showed a significant association with two loci haplotypes pertaining to BD, suggesting that this enzyme plays a role in the etiology of the disease [91], and, indeed, this isoform appears to be reduced in the temporal cortex of individuals with bipolar disorder [92], but α2 and α3 may be increased in the prefrontal cortex [20].…”
Section: Role Of Ecs In Humans Mood Disordersmentioning
confidence: 97%
“…When EO has been measured directly in the prefrontal cortex (PFC), it has been found to be at the same level as non-psychiatric controls; however, this finding appears to be driven by two outlier patients with EO levels more than three times higher than the average for the entire group [20]. Interestingly, smoking is associated with reduced PFC EO levels [20], and this is important because individuals with bipolar illness are more than twice as likely to smoke as the general population [93]; the smoking status of the two outliers is not known [20].…”
Section: Role Of Ecs In Humans Mood Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The α1 isoform exhibits both a pumping and signaling function, α2 plays a role in Ca 2+ signaling and cardiac contractility, and α3 is linked to cardiac hypertrophy [ 43 ]. Recently, Singh et al also reported a significant contribution of α subunit NKA isoforms in patients with bipolar disease, since changes in levels of particular subunits may alter levels of endogenous CGs and, thus, affect the disease development [ 44 ]. With knowledge of these facts, we must precisely consider the significance of the experimental data.…”
Section: Cellular Targets Of Cardiac Glycosidesmentioning
confidence: 99%
“…Malfunction of Na,K-ATPase in brain is probably involved in development of several neurological disorders. Post mortem studies of the Na,K-ATPase showed alterations in brains of patients suffering from various encephalopathies, like Alzheimer's disease [4,5], epilepsy [6] or bipolar disease [7]. For getting deeper insight into the molecular basis of neurodegeneration various experimental animal models were introduced.…”
Section: Introductionmentioning
confidence: 99%